Estudio para la reutilización de aguas grises producidas en el hogar, como agua de regadío en la casa prototipo del barrio Chan, cantón Latacunga, provincia Cotopaxi, 2015 - Armas Solís, Mario Ricardo (2015)
The investigation was carried out with the aim of improving the efficiency use of water for irrigation in the rural sector in the Cotopaxi province, to decrease the demand for drinking water. This work consists of research, analysis and implementation; in particular, corresponds to the design and implementation of treatment system used water. The proposed project was built in the restaurant "La Tonga", which is located in the sector Chan, in the province of Cotopaxi. During the design the hydraulic test was carried out to verify the capability and the system efficiency….